Analisis Pengaruh Manajemen Waktu, Motivasi Kuliah, dan Aktualisasi Diri Terhadap Prestasi Akademik Mahasiswa yang Bekerja (Studi pada Mahasiswa Jurusan Manajemen Fakultas Ekonomika dan Bisnis Universitas Diponegoro Semarang) - Andari, Novita Dwi; Nugraheni, Rini (Diponegoro Journal of Management, 2016)
This research aims to analyze the influence between time management, study motivation,  self actualization and student’s academic achievement who have part time job. The data in this research was collected through questionnaire distributed to 89 respondents, which are undergraduate students from Management Bachelor Degree in Diponegoro University. The techniques to testing data is multiple linear regression analysis. Results indicates that time management, study motivation, and self actualization give positive influence to academic achievement of undergraduate students in Management Bachelor Degree in Diponegoro University who have part time job. Those variables also give 67% contribution to the variety of  student’s academic achievement who have part time job.